2020
DOI: 10.1063/5.0029608
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular-rotation driven triplet-to-singlet upconversion and fluctuation induced fluorescence activation in linearly connected donor–acceptor molecules

Abstract: Thermally activated triplet-to-singlet upconversion is attractive from both fundamental science and exciton engineering, but controlling the process from molecular configuration is still unrevealed. In particular, the flexibility of the freedom of molecular geometry is of major importance to understand the kinetics of the phonon-induced upconversion. Here, we focus on two linearly connected donor–acceptor molecules, 9,9-dimethyl-9,10-dihydroacridine-2,4,6-triphenyl-1,3,5-triazine (DMAC-TRZ) and hexamethylazatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…These structural features are entirely different from typical D-A type TADF molecules we already reported 34,35 in which the structural change is small in the excited state. This rigidity must bring about the high oscillator strength and a narrow FWHM with a small Stokes shift of DABNA-1.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…These structural features are entirely different from typical D-A type TADF molecules we already reported 34,35 in which the structural change is small in the excited state. This rigidity must bring about the high oscillator strength and a narrow FWHM with a small Stokes shift of DABNA-1.…”
Section: Resultscontrasting
confidence: 98%
“…Here, we have investigated the excited-state geometries and molecular orbitals in DABNA-1 using TR-IR in conjugation with density functional theory (DFT) calculations and time-dependent (TD-) DFT calculations. Using the same method, we reported the correlations between structural dynamics and TADF activities 34,35 . Because the results of TD-DFT calculations strongly depend on a choice of functionals 36 , comparison to experimental data is essential.…”
Section: Introductionmentioning
confidence: 99%
“…According to the second-order spin-vibronic mechanism as discussed in section 2.2, the RISC process of TADF involves two triplet excited states vibronically coupled to each other, thus efficient TADF requires a certain degree of intramolecular vibrations, as demonstrated in many studies. [93][94][95][96] For example, Ward et al [94] found that by sterically hindering the intramolecular motion of the D and A groups, the emission of the materials could be switched from TADF to room temperature phosphorescence, which indicates that TADF depends on molecular vibrations. These results have quite beneficial implications for the choice or design of host materials in terms of their rigidity.…”
Section: Effects Of Host Rigiditymentioning
confidence: 99%
“…Time-resolved IR (TR-IR) spectroscopy, a powerful tool to obtain information about geometries of excited species, 22,[45][46][47] was carried out on 2Cz2SB in a benzene solution and KBr pellet. An FT-IR spectrum of 2Cz2SB in KBr contains multiple bands in the 1100-1400 cm À1 region (Fig.…”
Section: Time-resolved Irmentioning
confidence: 99%